Parasites of sheep at the International Livestock Centre for Africa Debre Berhan Station, Ethiopia - Njau, B.C.; Scholtens, R.G.; Kasali, O.B. (Elsevier, 1990)
Prevalence of gastrointestinal parasites was investigated using monthly faecal samples and necropsy data in sheep treated regularly and irregularly at ILCA, Debre Berhan station. Maximum infection rates with nematodes, fasciola and coccidia in the irregularly treated sheep were 18 percent, 10 percent and 37 percent, respectively, compared with 5 percent, 3 percent and 41 percent for the hosts treated regularly. Strongylosis was diagnosed mainly in July-Nov, fasciolosis in Jan-Jun and cocidiosis all the year round. Deworming with fenbendazole resulted in low worm -egg output and the abscence of helmianthiasis. Supplementary feeding of the untreated flock resulted in weight gains supirior to the treated group but at necropsy different species of helminth were encountered.